Dynamics of everyday practices of urban parents - Tatiana A. Gurko (Социологическая наука и социальная практика, 2024)
In order to further improve family policy, the article aims to analyze the dynamics of everyday practices of parents. The empirical basis is the databases on individuals of the Comprehensive monitoring of living conditions (GKS-KOUZH — 2011,2016, 2018, 2020, 2022 years), which is conducted by the Federal State Statistics Service. Subsamples of urban fathers and mothers living with children under the age of 15 have been formed. The daily practices of parents are analyzed based on the indicators of work, leisure, sports, health, smoking and alcohol consumption contained in the database, depending on gender, educational level and number of children. The article presents an analysis of studies on the transmission of constructive and destructive parenting practices to children. It is shown that during the analyzed period, the proportion of parents who work in their specialty, attend various leisure facilities, participate in the activities of political and public organizations, engage in sports and drink alcohol is stable. The proportion of mothers attending religious institutions and meetings of believers has decreased. There are positive trends in a significant increase in the proportion of both fathers and mothers who are satisfied with their profession and salary, who make tourist trips, who positively assess their health and a decrease in the proportion of fathers who smoke. According to the analysis of the KOUZH-2022, more parents with higher education work in their specialty, are satisfied with wages, have the opportunity to work distantly via the Internet, practice buying food and goods over the Internet, make tourist trips, visit the theater, museums, exhibitions, restaurants, participate in social activities, do not smoke, play sports or active recreation compared to parents without higher education. Parents with many children are similar in terms of types of professional activities and level of education to one- and two-child parents. The absolute advantage of parents with many children is a significant proportion of religious fathers and the lowest level of alcohol consumption by fathers and mothers. Positive trends in the daily activities of parents inspire optimism about the prospects for fertility and the quality of parenthood.